"Emergence of Multidrug Resistant Strains of Escherichia coli Isolated from Urinary Tract Infections" - R Moniri; A Khorshidi; H Akbari (Tehran University of Medical Sciences, 2003)
The emergence of multidrug resistant strains of Escherichia coli has complicated treatment decision and may lead to treatment failures. From April to November 2001 we prospectively evaluated the prevalence of resistance to trimethoprim-sulfamethoxazole (SXT), gentamicin, cephalothin, ciprofloxacin, and nitrofurantoin in 220 Escherichia coli isolates from patients with urinary tract infections in kashan, Iran. To assess the current breadth of multidrug resistance among urinary isolates of E. coli. of total isolates, 10.9% were resistant to three or more agents and considered multidrug resistant. Among the multidrug resistant isolates, 91.7% were resistant to SXT, 75% to gentamicin, 58.3% to cephalothin, 54.2% to ciprofloxacin and 45.8% to nitrofurantoin. The predominant phenotype among multidrug resistant isolates (29.2%) included resistance to SXT, gentamicin, and cephalothin. Rates of multidrug resistance were demonstrated to be higher among males (13.2%) than females (10.4%). There was no significant association between gender and reduced susceptibility. Continued local surveillance studies are urged to monitor emerging antimicrobial resistance and to guide interventions to minimize its occurrence.